Nucleolar protein NPM1 is essential for circovirus replication by binding to viral capsid. Issue 1 (1st January 2020) - Zhou, Jianwei; Dai, Yadong; Lin, Cui; Zhang, Ying; Feng, Zixuan; Dong, Weiren; Jin, Yulan; Yan, Yan; Zhou, Jiyong; Gu, Jinyan
ABSTRACT: Entry of circovirus into the host cell nucleus is essential for viral replication during the early stage of infection. However, the mechanisms by which nucleolar shuttle proteins are used during viral replication is still not well understood. Here, we report a previously unidentified nucleolar localization signal in circovirus capsid protein (Cap), and that circovirus hijacks the nucleolar phosphoprotein nucleophosmin-1 (NPM1) to facilitate its replication. Colocalization analysis showed that NPM1 translocates from the nucleolus to the nucleoplasm and cytoplasm during viral infection. Coimmunoprecipitation and glutathione S -transferase pull-down assays showed that Cap interacts directly with NPM1. Binding domain mapping showed that the arginine-rich N-terminal motif 1 MTYPRRR YRRRR HR PR SHLG 20 of Cap, and residue serine-48 of the N-terminal oligomerization domain of NPM1, are essential for the interaction. Virus rescue experiments showed that all arginine to alanine substitution in the N-terminal arginine-rich motif of Cap resulted in diminished viral replication. Knockdown of NPM1 and substitution of serine-48 in NPM1 to glutamic acid also decreased viral replication. In addition, binding assays showed that the arginine-rich motif of Cap is a nucleolar localization signal. Taken together, our findings demonstrate that circovirus protein Cap is a nucleolus-located, and regulates viral replication by directly binding to NPM1.